Intravital Imaging of Mesenchymal Stem Cell Trafficking and Association With Platelets and Neutrophils. (18th December 2014) - Teo, Grace Sock Leng; Yang, Zijiang; Carman, Christopher V.; Karp, Jeffrey M.; Lin, Charles P.
Abstract: Early events of mesenchymal stem/stromal cell (MSC) adhesion to and transmigration through the vascular wall following systemic infusion are important for MSC trafficking to inflamed sites, yet are poorly characterized in vivo. Here, we used intravital confocal imaging to determine the acute extravasation kinetics and distribution of culture-expanded MSC (2–6 hours postinfusion) in a murine model of dermal inflammation. By 2 hours postinfusion, among the MSC that arrested within the inflamed ear dermis, 47.8% ± 8.2% of MSC had either initiated or completed transmigration into the extravascular space. Arrested and transmigrating MSCs were equally distributed within both small capillaries and larger venules. This suggested existence of an active adhesion mechanism, since venule diameters were greater than those of the MSC. Heterotypic intravascular interactions between distinct blood cell types have been reported to facilitate the arrest and extravasation of leukocytes and circulating tumor cells. We found that 42.8% ± 24.8% of intravascular MSC were in contact with neutrophil-platelet clusters. A role for platelets in MSC trafficking was confirmed by platelet depletion, which significantly reduced the preferential homing of MSC to the inflamed ear, although the total percentage of MSC in contact with neutrophils was maintained. Interestingly, although platelet depletion increased vascular permeability in the inflamed ear, there was decreased MSC accumulation. This suggests that increased vascular permeability is unnecessary for MSC trafficking to inflamed sites. These findings represent the first glimpse into MSC extravasation kinetics and microvascular distribution in vivo, and further clarify the roles of active adhesion, the intravascular cellular environment, and vascular permeability in MSC trafficking. Stem Cells   2015;33:265–277